Expressions of Social Presence in Agricultural Conversations on Twitter: Implications for Agricultural Communications - Kelly M. Pritchett; Traci L. Naile; Theresa P. Murphrey (Journal of Applied Communications, 2012)
Computer-mediated environments such as social media create new social climates that impact communication interactions in un-mediated environments. As computer-mediated communication (CMC) stimulates more social communities, many communication behaviors will evolve and adapt to the unique social environment created by CMC. This study examined social variables during two different synchronous conversations on Twitter through a qualitative document analysis that coded messages into affective, interactive, and cohesive categories. Categories were determined by indicators within each message such as emoticons, direct responses, and the use of individuals’ names. The researcher concluded that most social variables in the Twitter conversations fit into the interactive social presence category but that affective and cohesive responses supported personal connection and structure within the conversations. It was also found that the same category of responses could function differently in each conversation. However, both conversations in this study appeared to be successful. Therefore, agricultural communicators should feel comfortable using CMC that contains social presence dimensions to circulate agricultural information among populations across the globe. Additional research should be conducted to examine social presence among new topics, populations, and other forms of CMC.
Keywords: Twitter; social presence; agricultural communications; social media; computer-mediated communication